Regenerative medicine: Hydrogels and mesoporous silica nanoparticles - Jesús L. Pablos; Daniel Lozano; Miguel Manzano; María Vallet-Regí (Materials Today Bio)
Hydrogels, that are crosslinked polymer networks, can absorb huge quantities of water and/or biological fluids. Their physical properties, such as elasticity and soft tissue, together with their biocompatibility and biodegradability, closely resemble living tissues. The versatility of hydrogels has fuelled their application in various fields, such as agriculture, biomaterials, the food industry, drug delivery, tissue engineering, and regenerative medicine. Their combination with nanoparticles, specifically with Mesoporous Silica Nanoparticles (MSNs), have elevated these composites to the next level, since MSNs could improve the hydrogel mechanical properties, their ability to encapsulate and controlled release great amounts of different therapeutic agents, and their responsiveness to a variety of external and internal stimuli. In this review, the main features of both MSNs and hydrogels are introduced, followed by the discussion of different hydrogels-MSNs structures and an overview of their use in different applications, such as drug delivery technologies and tissue engineering.